Evaluation of environmental factors and microbial community structure in an important drinking-water reservoir across seasons - Feng, Jie; Zhou, Letian; Zhao, Xiaochao; Chen, Jianyi; Li, Zhi; Liu, Yongfeng; Ou, Lei; Xie, Zixin; Wang, Miao; Yin, Xue; Zhang, Xin; Li, Yan; et al. (Frontiers in Microbiology, 2023)
The microbial community composition of water differs from sediments, and the dynamics of the environmental factors could be crucial for microbiomes. In this work, we profiled microbial communities and physicochemical factors at two sites in a large subtropical drinking water source reservoir in southern China. All sites' microbiomes (diversity and abundance) were determined via metagenomics, and the relationship between microbiomes and physicochemical factors was investigated by redundancy analysis. The results showed that the dominant species in sediment or water samples differed, with the former being Dinobryon sp. LO226KS and Dinobryon divergens and the latter being Candidatus Fonsibacter ubiquis and Microcystis elabens. The diversity was also significantly different through alpha diversity analysis (P = 0.0028). The trophic level index (TLI) was the major factor affecting the microbial community in water samples; the bacterial species Mycolicibacterium litorale and Mycolicibacterium phlei were significantly positively related to TLI. Multidrug resistance genes were the most abundant in sediments or water samples. Algal toxins encoding genes were more abundant in water than in sediment samples, with cylindrospermopsins having the highest gene abundance. This study promotes an understanding of how environmental factors affect microbiomes. Physicochemical properties of water quality and microbial community studies will enable water quality monitoring and conservation.